Modeling the evolution of expectations and uncertainty in general equilibrium - Francesco Bianchi; Leonardo Melosi (Federal Reserve Bank of Chicago, 2013)
We develop methods to solve general equilibrium models in which forward-looking agents are subject to waves of pessimism, optimism, and uncertainty that turn out to critically affect macroeconomic outcomes. Agents in the model are fully rational, conduct Bayesian learning, and they know that they do not know. Therefore, agents take into account that their beliefs will evolve according to what they will observe. This framework accommodates both gradual and abrupt changes in beliefs and allows for an analytical characterization of uncertainty. Shocks to beliefs affect economic dynamics and uncertainty. We use a prototypical Real Business Cycle to illustrate the methods.
Keywords: D83; C11; E22; 330; Markov switching; general equilibrium models; uncertainty; Bayesian learning; rational expectations; downside risk; rare disasters